Pressure drops of air-water two-phase flows in horizontal U-bends. (October 2020) - Hayashi, Kosuke; Kazi, Junichiro; Yoshida, Naoyuki; Tomiyama, Akio
Highlights: Experiments on pressure drops in two-phase flows in U-bends are carried out. Bend pressure drops in an air-water system are compared with available correlations. Bubbly, plug, slug and annular flows are dealt with. A Chisholm-type bend pressure drop correlation is presented. Abstract: Pressure drops in horizontally aligned U-bends were measured for air-water bubbly, plug, slug and annular flows to examine the applicability of available correlations to the data. The bend disturbed the flow and induced large pressure drops not only within the bend but also in the downstream-side straight pipe. The bend pressure drop was therefore evaluated as the sum of the pressure drop caused within the bend and the extra pressure drop caused within the re-developing region in the downstream-side straight pipe. The experimental data were well correlated using the Lockhart-Martinelli method and the Chisholm correlation gives the most reasonable evaluation for the bend pressure drop among the available correlations tested. The fundamental functional form of the Chisholm correlation was therefore used to develop an empirical correlation applicable to the present data. The empirical correlation gave reasonable evaluations for the air-water two-phase flows.